RANCANG BANGUN SISTEM INFORMASI AKADEMIK MENGGUNAKAN PHP DAN MYSQL (Studi Kasus pada Fakultas Teknik Universitas Lampung) - Ruwandar, Heru; Priyadi, R. Arum Setia; Fitriawan, Helmy (Jurnal Informatika dan Teknik Elektro Terapan, 2013)
AbstractStarting from 2000, the Academic Information System (SIAKAD) could be accessed on-line by the entire academic community of the University of Lampung. SIAKAD used for academic purposes at the University of Lampung, such as card-making Plan Study (KRS), and Study Result Card (KHS). Faculty of Engineering, University of Lampung, which is one of the faculty who are in the shade of the University of Lampung also been wearing SIAKAD on-line for academic administration for its students. But in reality, SIAKAD on-line that used still had some shortcomings, namely, the absence of a recapitulation of how many students pass a graduation period, the average GPA of a graduation, the average GPA per class, how many students graduate, active, Drop Out (DO) a generation in one department, and the average of study period per period graduates. Therefore, in this study there had been made academic information system contains solutions to some of the shortcomings of the SIAKAD on-line used by the University of Lampung and were focused only on the Faculty of Engineering, University of Lampung. The information system was built using the programming language PHP version 5.3.5 and MySQL version 5.0.7 as its DBMS. At first the information system was created on the local host server and then uploaded to the web server of the Faculty of Engineering, University of Lampung. Once the information system was built, the system tested. Testing was done by two scenarios, namely offline scenario and online scenario. In the offline testing, information system that was built could show how average GPA per class, average GPA per period of graduation, student statistics, as well as how many students were active, graduated, not graduated, dropped out (DO), and resigned themselves. Online scenario was done after the system information uploaded to the web server of the Faculty of Engineering. All existing features were also working as intended.Keywords: SIAKAD, information system, modified waterfall, localhost server.